PSEN1 is associated with colon cancer development via potential influences on PD-L1 nuclear translocation and tumor-immune interactions - Wei, Wangzhi; Zhang, Yu (Frontiers in Immunology, 2022)
Presenilin 1 (PSEN1), as a catalytical core of the γ-secretase complex, plays multiple actions through mediating transmembrane domain shedding of the substrates. Unlike extensive studies performed on investigating the functions of γ-secretase substrates or the effects of γ-secretase inhibitors, our findings uncover a potential action of PSEN1 on PD-L1 alternative truncation and nuclear translocation, broadening our understanding on how the γ-secretase contributes to colon cancer development as well as suggesting a potential strategy to improve the efficacy of PD-1/PD-L1 blockade. Immunohistochemical data showed loss of PD-L1 protein expression in all the primary colon adenocarcioma (COAD) cases in the HPA collection, while PSEN1 was scored to be highly expressed, indicating their converse expression patterns (p<0.001). Meanwhile a strongly positive gene correlation was explored by TIMER2 and GEPIA (p<0.001). Up-regulated PSEN1 expression in COAD might facilitate liberating a C-terminal PD-L1 truncation via proteolytic processing. Then following an established regulatory pathway of PD-L1 nuclear translocation, we found that PSEN1 showed significant correlations with multiple components in HDAC2-mediated deacetylation, clathrin-dependent endocytosis, vimentin-associated nucleocytoplasmic shuttling and importin family-mediated nuclear import. Moreover, connections of PSEN1 to the immune response genes transactivated by nuclear PD- L1 were tested. Additionally, contributions of PSEN1 to the tumor invasiveness (p<0.05) and the tumor infiltrating cell enrichments (p<0.001) were investigated by cBioportal and the ESTIMATE algorithm. Levels of PSEN1 were negatively correlated with infiltrating CD8+ T (p<0.05) and CD4+ T helper (Th) 1 cells (p<0.001), while positively correlated with regulatory T cells (Tregs) (p<0.001) and cancer associated fibroblasts (CAFs) (p<0.001). It also displayed significant associations with diverse immune metagenes characteristic of T cell exhaustion, Tregs and CAFs, indicating possible actions in immune escape. Despite still a preliminary stage of this study, we anticipate to deciphering a novel function of PSEN1, and supporting more researchers toward the elucidations of the mechanisms linking the γ-secretase to cancers, which has yet to be fully addressed.